P5.082 What Are the Costs and Benefits of Implementing Point of Care Tests For Chlamydia Trachomatis and Neisseria Gonorrhoeae in Genitourinary Medicine Clinics?. (13th July 2013) - Turner, K M; Round, J; Deol, A; Horner, P; Macleod, J; Goldenberg, S; Adams, E
Abstract : Background: To estimate the costs and benefits of new patient pathways in genitourinary medicine (GUM) clinics that incorporate a point of care (POC) nucleic acid amplification test (NAAT) for chlamydia and gonorrhoea (CT/NG), compared to standard off-site laboratory testing. Method: We modelled 20, 000 GUM clinic attendees, based on GUMCAD reported diagnoses for men and women in England (2011). A Markov model with Monte Carlo simulation in Excel was developed. We compared existing standard pathways of testing and treatment using a CT/NG test with a new POC NAAT. Scenario and sensitivity analyses were conducted to evaluate the robustness of the model findings. The primary outcome was incremental cost effectiveness ratio (ICER, £ per QALY) of testing and treatment in GUM clinics. Secondary outcomes included the number of overtreatments for CT/NG, complications and transmissions averted, and change in time from test to treatment. Results: The total cost of using the CT/NG POC NAAT in 20, 000 patients was £1.73 million and £1.92 million for standard care. The new POC NAAT pathway dominated (less expensive and increased QALYs, ICER of £4, 397/QALY saved). As many as 541 unnecessary treatments could be prevented using POC NAAT. The shorter time to treatment for patients receiving same-day diagnosis and treatment may also prevent a small number of complications (3.4 cases PID) and onward transmissions (31.9 infections). Discussion: Replacing standard laboratory tests for CT/NG with a POC NAAT seems to be cost saving or at least cost neutral, and patients would benefit from more accurate diagnosis and less unnecessary treatment. POC NAATs would effectively eliminate the need for presumptive treatment.